The Effect of Flame Treatment on Surface Properties and Heat Sealability of Low‐Density Polyethylene Coating. (14th May 2012) - Tuominen, Mikko; Ek, M.; Saloranta, P.; Toivakka, M.; Kuusipalo, J.
Abstract : The target of this study is to investigate the correlation between surface properties and heat sealability of flame‐treated low‐density polyethylene (LDPE) coating because it is vital to know how to modify the surface properties of LDPE coating without losing the heat sealing properties. Flame treatment showed a significant effect on the heat sealing properties of LDPE‐coated paper. For example, the heat sealing temperature of LDPE coating decreased or alternatively doubled, depending on the equivalence ratio (air–propane ratio) of flame treatment. In addition, the hot tack strength was significantly enhanced by flame treatment, which broadened the hot tack window of LDPE‐coated paper. The reason for the heat sealing performance of flame‐treated LDPE coating was believed to be related to the simultaneous reactions, that is, cross‐linking and chain scission, occurring on the LDPE surface. The molecular weight of LDPE surface increased or decreased, depending on the dominating reaction during flame treatment. This affected the chain mobility and the amount of chain interdiffusion across the seal interface and finally defined the heat sealing performance of LDPE‐coated paper. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : The study shows how the heat sealability of LDPE‐coated paper can be enhanced or alternatively deteriorated, depending on the equivalence ratio of flame treatment. For example, the increased seal strength at the hot tack temperatures of 50 °C to 80 °C expanded the hot tack window of LDPE‐coated paper significantly, even at the line speed of 300 m/min. The reason for the heat sealing performance of flame‐treated LDPE coating is believed to be related to the simultaneous reactions, that is, cross‐linking and chain scission, on the surface of LDPE‐coated paper.